Entrainment dominates the interaction of microalgae with micron-sized objects - Raphaël Jeanneret (Nature Portfolio, 2016)
Passive particles surrounded by swimming protists diffuse tens of times faster than their thermal motion, which might have an impact on microscopic predator-prey interaction in nature. Here, Jeanneret et al.investigate its physical origin and identify direct particle entrainment as the dominant feature.